How user-generated content advertising influences consumer attitudes, trust and purchase intention of products and services - Diana Demba; Norman Chiliya; Tinashe Chuchu; Tinashe Ndoro (Communicare)
Due to the rapid advancement of new technologies in business, marketers’ dependency on usergenerated content (UGC) is rising. This study therefore seeks to elucidate the importance of usergenerated content in creating sales and establishing relationships with customers. Convenience non-probability sampling was adopted in selecting 330 participants. In addition, structural equation modelling was used in testing proposed hypotheses. Findings reveal that there is a positive relationship between the use of UGC, brand trust and purchase intention. However, it is observed that subjective norms, information quality and source credibility affect the use of UGC for decision making. The main recommendation is that it is imperative for marketers to be cognisant of their online audience and engage with customers online. Overall, this study will aid marketers in the comprehension of the factors associated with brand trust and purchase intention in relation to UGC advertising.